PERTANGGUNGJAWABAN NEGARA PENERIMA TERHADAP TERBUNUHNYA DUTA BESAR AMERIKA SERIKAT DAN KERUSAKAN GEDUNG KEDUTAAN BESAR AMERIKA SERIKAT DI LIBYA - Dhoti Prihanisa Auliya, Peni Susetyorini, Muchsin Idris*) (Diponegoro Law Journal, 2013)
Diplomacy offers the opportunity to avoid conflict or at least minimize its impact. Diplomatic relations are conducted by the ambassador holds a very important role in various aspects of national life, the safety and security they should be strictly protected. But the event of the murder of U.S. Ambassador to Libya, John Christopher Stevens, in Benghazi Libya, a bad experience for the diplomatic world. Libya as Receiving State impressed negligent in making efforts to protect foreign missions in the country, as mandated by the Vienna Convention on Diplomatic Relations 1961. In addition to ambassadors and killed several U.S. citizens, U.S. foreign representative offices in Libya was also damaged by the massive demonstrations protesting the movie Innocence of Muslims.